The short‐ and long‐term outcomes of pancreaticoduodenectomy for cancer in child a patients are acceptable: A patient‐control study from the Surgical French Association report for pancreatic surgery. Issue 6 (8th February 2015) - Regimbeau, Jean‐Marc; Rebibo, Lionel; Dokmak, Safi; Boher, Jean‐Marie; Sauvanet, Alain; Chopin‐Laly, Xavier; Adham, Mustapha; Lesurtel, Mickaël; Bigourdan, Jean‐Marc; Truant, Stéphanie; Pruvot, François‐René; Ortega‐Deballon, Pablo; et al.
Abstract : Background: On the basis of now dated studies, cirrhosis is usually considered to be a contraindication in pancreatoduodenectomy (PD) for adenocarcinoma of the pancreatic head (APH). Objective: Examine the outcomes of PD for APH in the presence of cirrhosis. Methods: Retrospective, multicenter study of cirrhotic patients with APH having undergone PD between January 2004 and March 2012. Cirrhotic patients were matched 1:2 for demographic, surgical and histologic criteria with non‐cirrhotic patients. Primary endpoint was morbidity and mortality. Secondary endpoints were surgical parameters, morbidity related to pancreatic surgery and cirrhosis, and follow‐up. Results: We included 35 patients with cirrhosis. Twenty‐four patients (69%) were Child A and none were Child C. The Child A cirrhotic patients and non‐cirrhotic patients respectively had complication rates of 79% vs. 43% ( P   = 0.002), major complication rates of 33% vs. 21% ( P  = 0.26), pancreatic fistula rates of 13% vs. 9% ( P   = 0.57), post‐operative mortality of 4% vs. 5% ( P   = 0.94), 3‐year overall survival rates of 44% vs. 50% ( P   = 0.46). All Child B cirrhotic patients experienced post‐operative complications. Conclusion: Pancreatoduodenectomy for APH was possible in Child A cirrhotic patients with a mortality and long‐term outcomes equivalent to non‐cirrhotic patients. Child B cirrhosis remains a clear contraindication to surgery. J. Surg. Oncol. 2015 111:776–783 . © 2015 Wiley Periodicals, Inc. J. Surg. Oncol. 2015 111:776–783 . © 2015 Wiley Periodicals, Inc.